REGISTERS USED IN BANGKIT COMMUNITY OF PT DUTA NETWORK INDONESIA - RINALDY, FERY INDRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keyword : Sociolinguistics, Registers, Network Marketing, PT. Duta Network  Indonesia, Bangkit Community.One of the characteristics of human being is that human has language and use language for communication. As s social being, communication is the most important way to create the society. People create society based on region, interest, social class, religion and many others. In spesific group people create their own terms in their community and it is called register. In this study, the writer conducted a study about register used by network marketing company members in PT. Duta Network Indonesia. There are two problems of the study, they are (1) What are the registers used by member of Bangkit community in PT. Duta Network Indonesia (DNI)?; (2) What are the meanings of register used by member of Bangkit Community in Duta Network Indonesia (DNI)?In this study, the witer used descriptive qualitative aproach with homogeneous purposive sampling. The data were conversation between the leader and member  and the speaker explanation in the meeting. Data source was in small meeting and public training of Bangkit community in PT. Duta Network Indonesia discussing success plan knowledge and recruiting strategy topics. The writer described the contextual analysis of the conversation where the registers used by the members.The writer found around 30 registers used by the members of network marketing company in PT. Duta Network Indonesia. Some of the registers have common sense some do not. Then, some registers especially the grade in Bangkit community in PT. Duta Network Indonesia such as, Star Leader, Top Leader, Exclusive Leader, Master leader and King Master Leader. PT. Duta Network Indonesia makes carrier level based on the meaning of each words. King Master has the highest meaning, therefore it is always at the top of the levels after Master, Exclusive, Top and Star. Generally the writer found most of the contextual factors influencing the speakers are about carrier levels and marketing strategies. The situation is when the leaders share information in purpose to make the other members feel enthusiastic to attain next level.The registers used by Network Marketing comapny members in PT. Duta Network Indonesia has relation with the marketing strategies and the carrier level and the training in their business. Those registers are important knowledge to rech success in the business. The writer suggests for the next writer to analyze register in other business community because business field is the interesting subject. It can give information, not only for English students but also for other people who need business information.